(untitled) (Ameghiniana, 2017)
This paper presents the remains of Migadops latus, the first fossil insect extracted from the peat bogs of Tierra del Fuego Island, at the southernmost extreme of Patagonia. The presence of this species supports the environmental interpretations that propose an increase in humidity and the advance of a closed Nothofagus forests around 3000 years BP. This finding is the first step in the characterization of the Quaternary paleoentomofauna of Tierra del Fuego setting the beetles as bioproxies for paleoclimatic studies in the southernmost area of South America.